Pengukuran Kinerja Perbankan Sebelum dan Sesudah Menerapkan Teknologi Blockchain: Studi Kasus pada Bank BUMN yang Menerapkan Teknologi Blockchain Periode 2017-2024 - Aura Restu Anindya Putri; Hermawan Triono; Enny Susilowati Mardjono (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study is to examine the differences in financial performance before and after the application of blockchain technology to BUMN Bank. This researcher used a quantitative approach with secondary data in the form of state-owned bank financial statements for the 2017-2024 period. Variables analyzed include Return On Asset (ROA), Return On Equity (ROE), Net Interest Margin (NIM), and Operational Cost and Revenue (BOPO) with Shapiro-Wilk normality test, Paired Sample-test, and Wilcoxon Signed Rank Test. Research results show that implementing blockchain does not have a significant effect on ROA and ROE. Meanwhile, the ratio of NIM and BOPO was found to have a significant influence only on Bank Negara Indonesia (BNI) and Bank Mandiri, while other state-owned banks did not show a significant difference. This indicates that the impact of blockchain on the profitability and efficiency of state-owned banks is still limited because this technology is relatively new so that its benefits are not fully reflected on financial performance. Based on the analysis results in this study, it is shown that banks need to adjust their business strategies by utilizing blockchain for operational efficiency, service innovation, and improved security and transparency to maintain sustainable competitiveness and profitability.